The Role of Principal Leadership, Work Culture, and Work Motivation in Enhancing Digital Literacy Among Public Junior High School Teachers in Boja District - Barokah Guniarti; Ngurah Ayu Nyoman; Dyah Nugrahani (STAI Hubbulwathan Duri, 2025)
Digital literacy has become a crucial competence for teachers to ensure the quality of education in the digital era. This study examines the influence of principal leadership, work culture, and work motivation on the digital literacy of teachers in public junior high schools in Boja District. A quantitative approach with a correlational design was employed, involving 105 teachers selected through proportional random sampling. Data were collected using a validated and reliable questionnaire and analyzed through regression techniques after meeting prerequisite statistical tests. The results indicate that principal leadership, work culture, and work motivation each have a significant effect on teachers’ digital literacy, contributing 56.4%, 51.3%, and 49.8% respectively. When tested simultaneously, these three factors explain 71% of the variance in digital literacy, underscoring the importance of a comprehensive approach to strengthening teachers’ digital competencies. The findings suggest several practical implications. Transformational school leadership, innovation-oriented work culture, and motivational support through recognition and professional development are essential in fostering digital literacy. Schools with limited resources may adopt community-based training, while better-equipped schools can expand the integration of digital technologies into learning. This study contributes empirical evidence on the relationship between leadership, culture, and motivation in developing teachers’ digital competencies. Future research is recommended to investigate additional factors such as infrastructure, policy, and professional learning communities using experimental or longitudinal designs to assess the effectiveness of interventions.